1996
DOI: 10.1016/s0022-5347(01)65749-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Estrogen Receptor Expression in Human Prostatic Stromal Cells by Androgen Ablation Therapy

Abstract: Androgen deprivation leads to an upregulation of stromal ER expression in human prostate. Estrogen-induced morphological epithelial changes could be explained by a paracrine interaction between stromal and epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…This close relationship between the two classes of receptor has been demonstrated in cultured human prostatic stromal cells in which exposure to estradiol also raised the level of AR. 6 A similar phenomenon has also been reported in cultured prostatic carcinoma cell lines, 28 in stromal cells of prostatic carcinoma from patients treated with androgen ablation therapy 10 and in castrated dogs treated with oestrogen. 5 Culture of stromal cells with different concentrations of estradiol and testosterone, produced no consistent pattern of ERa and AR expression between the various treatments.…”
Section: Discussionsupporting
confidence: 74%
“…This close relationship between the two classes of receptor has been demonstrated in cultured human prostatic stromal cells in which exposure to estradiol also raised the level of AR. 6 A similar phenomenon has also been reported in cultured prostatic carcinoma cell lines, 28 in stromal cells of prostatic carcinoma from patients treated with androgen ablation therapy 10 and in castrated dogs treated with oestrogen. 5 Culture of stromal cells with different concentrations of estradiol and testosterone, produced no consistent pattern of ERa and AR expression between the various treatments.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies have demonstrated high levels of oestrogen receptors (ER) in human hyperplastic prostates which are located predominantly within cells of the stroma. [3][4][5] These stromal ER are of the alpha subtype, 3,4,6 the beta subtype being not detected immunohistochemically or flow cytometrically (as confirmed by preliminary studies for this investigation). In addition to their complement of androgen receptors (AR) and ERa, stromal cells also synthesise growth factors 7,8 by a process controlled by binding of androgens to AR.…”
Section: Introductionsupporting
confidence: 63%
“…Taken together, these findings suggest that flutamide may have testosteroneindependent affects on splenocytes. In fact, androgen depletion by castration or flutamide treatment has been shown to increase estrogen receptor expression in a variety of cells, including T cells (West et al 1990, Bodker et al 1994, Kruithof-Dekker et al 1996, Samy et al 2000. Furthermore, preliminary studies suggest that, not only are estrogen concentrations increased after burn as previously reported (Woolf et al 1985, Lephart et al 1987, but flutamide treatment further augments this increase (K A N Messingham, M A Emanuele and E J Kovacs, unpublished observation).…”
Section: Discussionmentioning
confidence: 65%